Antimicrobial Activity of the Extracts of Salacia oblonga Wall. - Archana Giri, M. Jayaram Prakash Rao and (Recent Research in Science and Technology, 2010)
Salacia oblonga Wall. belonging to the family celastraceae is used in the treatment of diabetes, rheumatism, gonorrhoea, itches, asthma, wound healing, amenorrhea and ear diseases. It is a woody climber distributed in Sri Lanka and Southern regions of India. In the present study antimicrobial activity of Salacia oblonga was evaluated against pathogenic strains, gram +ve Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis, Bacillus subtilis, Listeria monocytogenes and gram -ve Klebsiella pneumoniae, Enterobacter aerogenes, Enterobacter cloacae, Pseudomonas aeruginosa, Escherichia coli, Salmonella typhimurium. Ethyl acetate (EtOAc) aerial and root part extracts of Salacia oblonga have shown good activity towards all the pathogenic species. The zones of inhibition in the acidic EtOAc aerial and root extracts were measured to assess the antimicrobial activity.